Two new species of the family Niphatidae van Soest, 1980 from Northeastern Brazil (Haplosclerida: Demospongiae: Porifera) - Santos, George Garcia; Docio, Loyana; Pinheiro, Ulisses (Zootaxa, 2014)
This paper deals with niphatid sponges from the coast of the Bahia State, northeastern coast of the Brazilian shelf (southwestern Atlantic). Two new species are described, Amphimedon estelae sp. nov. and Niphates luizae sp. nov. A taxonomic study of those samples is given, including description and illustrations. Both species were compared with their congeners present in the Atlantic Ocean.